Analisis Kemampuan Mahasiswa Calon Guru Biologi Dalam Menyusun Rencana Pelaksanaan Pembelajaran (RPP) Dan Keterampilan Dasar Mengajar (KDM) Melalui Simulasi Pembelajaran - Triana Ahriza; Sulistyono Sulistyono; Asep Ginanjar Arip (Edubiologica Jurnal Penelitian Ilmu dan Pendidikan Biologi, 2019)
This research is entitled "Analysis of the Capability of Prospective Teachers of Biology in Developing Learning Implementation Plans (LIP) and Teaching Basic Skills (TBS) Through Learning Simulation on the Concept of the Human Circulatory System". This study aims to analyze the completeness of the components in the LIP, the suitability of the contents of LIP, TBS, and learning outcomes or learning outcomes in the subject of Teaching and Learning Strategies (TLS) and Animal Physiology. The research method used is descriptive research method using a qualitative descriptive research design. The population or social situation in this study are prospective students of Biology teacher at Galuh Ciamis University in semester IV of Academic Year 2017/2018 who follow the subject of Teaching and Learning Strategies and Animal Physiology. The results of the study show that (1) the completeness of the components in the LIP compiled by biology prospective students is dominant in the criteria of "Good" or declared "Competent" that is equal to 65.72% and the criteria of "Good" or "Excellent" is 34.28%, (2) the suitability of the LIP content compiled by biology prospective students is dominant in the criteria of "Enough" or "Must Be Improved" that is equal to 62.86% and the criteria of "Good" or "Competent" are 37.14%, (3) TBS owned by biology prospective student students is stated dominant in the criteria of "Enough" or "Beginner" that is equal to 62.86% and criteria "Good" or "Competent" of 37.14%, (4) Learning Outcomes or learning outcomes TLS subjects dominant on the criteria "Good" that is equal to 77.14%, on the criteria "Enough" of 20%, and on the "Very Good" criteria of 2.86%. Whereas for the academic value of Animal Physiology, it is dominant in the criteria of "Good" that is equal to 85.71%, the criteria for "Enough" is 8.57%, and the criteria for "Very Good" is 5.72%Keywords: Learning Implementation Plan; Basic Teaching Skills; Teaching and Learning Strategies